Causes of Abroad Study in Higher Education from Nepal - Mahatara, Tekendra Kumar (KMC Journal, 2024)
This study explores the factors that motivate Nepali students to study abroad as well as the obstacles they face in order to understand this phenomenon. Every year, the number of students going to study abroad from Nepal is increasing. Considering this situation, this study tries to find out why Nepali students choose to pursue their higher education overseas. A quantitative approach using surveys was used to acquire opinions from one hundred Nepali students. The findings indicate a significant propensity to study overseas in order to advance professionally, advance personally and obtain better employment prospects. Concerns regarding Nepal’s political unrest and lack of employment opportunities also play a role in decision-making for abroad study. These results highlight the complex interplay between socio-political, economic and personal factors when influencing decisions about educational migration. In order to meet the various needs of Nepali students and improve the regional educational system, policymakers and educational institutions must have a thorough understanding of these dynamics. Considering all things, the study adds to the conversation about globalization, educational mobility and the goals of young people in Nepal in an increasingly interconnected world.